IMPLEMENTATION OF THE ADDIE MODEL FOR DEVELOPING MULTIMEDIA LEARNING MEDIA AND GAMIFICATION ON SPACE OBJECTS MATERIAL IN ELEMENTARY SCHOOL - Firdaus, Rangga; Firdaus, Riyadh (Jurnal Teknik Informatika (Jutif), 2024)
Teaching material in learning outer space objects (PBLA) is an interesting and important topic for elementary school students to master. However, traditional methods in PBLA learning are often ineffective in increasing students' awareness and interest. Interactive multimedia learning uses a variety of technologies such as video images, and animation, as well as gamification elements such as points, levels, and rewards. Therefore, this research focuses on developing interactive multimedia learning and gamification to increase elementary school students' awareness and interest in PBLA. This research is research into the development of learning media using the 4D Method (Define, Design, Develop and Disseminate) type Research and Development (R&D) and conducting field tests in class VI UPTD SDN 40 Negeri Katon. The research results showed that the validity of interactive PowerPoint learning media based on a scientific approach in learning material at UPTD SDN 40 Negeri Katon elementary school was based on the results of an assessment from media experts of 94.45% and an assessment of material experts of 97.45% in the very appropriate/very valid category. The practicality of learning media is stated to be practical based on the suitability of the material provided. This is proven by the teacher response results being 98% and the student response results being 100%. This research produces gamification learning media using interactive PowerPoint based on a scientific approach that is valid and practical to use. It is hoped that the results of this research can contribute to the development of more effective and interactive curriculum and learning methods to increase students' awareness and interest in PBLA material.